Synthesis of a novel bifunctional photoinitiator: Hybrid coatings on polycarbonate - KAHRAMAN, MEMET VEZİR; KAYAMAN APOHAN, NİLHAN; BOZTOPRAK, YALÇIN (WILEY-V C H VERLAG GMBH, 2007)
The objective of this study was to synthesize a new bifunctional photoinitiator by the reaction between 1-hydroxy-cyclohexyl-phenyl-ketone and 3-isocyanato propyl trimethoxysilane (ICPTMS) and examine its capability in the photoinitiation process comparing it with the unmodified photoinitiator. This new photoinitiator also acts as a coupling agent for inorganic and organic phases. Therefore, its effect on the physical and mechanical properties of UV-curable transparent organic-inorganic hybrid coatings was investigated. The presence of the new bifunctional photoinitiator and TEOS, increased the abrasion resistance and also improved the hardness of the polymeric films.
Keywords: bifunctional photoinitiator; coatings; polycarbonates; UV-curable hybrid coatings